TRP Channels in Sensory Transduction - Madrid, Rodolfo; Bacigalupo, Juan (Springer International Publishing : Imprint: Springer, 2015)
TRP channels play a key role in sensory physiology and have been the focus of intensive investigation in recent years. This book is a comprehensive, detailed overview of the ways in which TRP channels are involved in a wide variety of sensory modalities. Authors explore the involvement of TRP channels in phototransduction (sight), chemotransduction (taste and odor), mechanotransduction (touch and hearing), thermotransduction (the sensation of temperature), and pain perception. Furthermore, the book includes some grounding chapters such as one on the history of TRP channel research, one on the biophysical characteristics of the proteins, and one on trafficking and post-translational regulation.